Género y delito: un estudio a partir de la delincuencia femenina en Trujillo 1950 - 1955. - Rivadeneyra Arce, Sofía María de Fátima (2016)
The present study aimed to analyze and define the criminal behavior of the Trujillo_x000D_ women during the years 1950-1955. Data that we have to propose that the increase of_x000D_ crimes carried out by women, at this juncture in particular, is linked to the impact that_x000D_ begin to have the ideas of women's liberation in local spaces, as it is the case of_x000D_ Trujillo, which was expressed by the women of lower classes through the crime_x000D_ unconsciously. In addition to the problem of gender, in our work, we will introduce_x000D_ current sociological categories of female criminality to a specific historical process.